Take control of Find My and AirTags - Fleishman, Glenn (Take Control Books, 2022)
Track your stuff, find your friends, and safely share your location Version 1.3, updated August 26, 2022 Take Control of Find My and AirTags takes you inside Apple's Find My ecosystem. Once a way to track the whereabouts of your iPhone by having it ping the internet at regular intervals, now Find My encompasses sharing and following people (with permission), much of Apple's hardware and some Beats audio gear, and new trackers from Apple and third parties (including the AirTag). This book helps you understand how it all fits together, and how to keep yourself safe by preventing, identifying, and blocking unwanted tracking. Since the introduction of Find My iPhone over a decade ago, Apple has made it possible to Find My Nearly Everything. The current ecosystem encompasses people, Apple devices, and low-power, long-life trackers. Take Control of Find My and AirTags takes you through the many parts of Find My so you can configure and refine how you and your stuff is tracked and shared. The book looks at three different kinds of tracking: People: Learn how to share your location safely, follow others who let you, and send and receive notifications about arrivals and departures. Devices: Apple lets you track the whereabouts of your and Family Sharing group members' iPhone, iPad, iPod touch, Mac, Watch, AirPods (all models), and Beats audio hardware (some models). Get to know the ins and outs of enabling Find My and taking remote actions, from playing a sound to wiping your data from a device. Items: Find out how AirTags make use of the crowdsourced network of other people's Apple devices to help you find a lost or forgotten purse, backpack, or even car, and about third-party devices licensing the technology from Apple. Also get to know the dangers of Find My stalking and how to identify the risk, deter unwanted tracking from happening, block it if you find it--and report it to law enforcement or get other help. The book also digs into how Family Sharing interacts with personal and device location sharing and finding, and how to help other people find their lost stuff if they don't have one of their own Apple devices handy. Covered operating systems are iOS and iPadOS versions 13 through 16, and macOS 10.15 Mojave through macOS 13 Ventura--and all the new options introduced in the latest releases of each. Here's more of what you can find in this book: Find out the difference between device-based Find My tracking and the Find My network. Figure out if your Apple or Beats audio hardware can be tracked just over Bluetooth nearby or via the Find My Network. Experience the joy of playing a sound over the internet or nearby to help find a missing device or item. See the place in Apple's ecosystem for third-party Find My tracking from Belkin (earbuds), Chipolo (ONE Spot tracker), and VanMoof (ebikes). Control and monitor the way you let others track your whereabouts. Get to know presence, the way you define which of your devices indicates where you are to other people. Learn about the capability in iOS 15/iPadOS 15 and later to track an iPhone or iPad even after it's been erased! Dig into Apple's efforts to prevent Find My from being used for stalking and unwanted tracking, and how to find out if someone's trying to track you without your permission. Discover buried controls for configuring exactly how Find My updates your device's location, including when power runs low. Understand Activation Lock, which protects devices from being reused even if someone has erased them. Help family members find lost and stolen gear through Find My's Family Sharing support. Revel in an expanding list of iOS, iPadOS, and macOS features that improve Find My's capabilities.